The relationship of male condoms and withdrawal contraceptive methods with female sexual function and satisfaction: a cross sectional study - Tadayon, Mitra; Honarjoo, Maryam; Abbaspoor, Zahra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Men’s participation is an important issue in family planning and reproductive health. Coitus interruptus and condom use are two reversible and non-hormonal methods of contraception to engage men in family planning. The present study is aimed to evaluate the relationship of male condom use and withdrawal as contraception with female sexual function and satisfaction. Methods: A cross-sectional study was conducted on 215 married women aged 15-45 years in Ahvaz. Necessary data were collected using three demographic, female sexual function index (FSFI), and female sexual satisfaction questionnaires. The data were analyzed using SPSS software version 22 and descriptive and analytical tests (independent t-test and Pearson’s and Spearman’s correlation coefficients) were used. A P level of less than 0.05 was considered significant. Results: Although there was no significant difference in the areas of sexual desire (p=0.31), sexual arousal (p=0.18), vaginal lubrication (p=0.63), and pain (p=0.06) between two groups, but significant differences were found between the areas of orgasm (p=0.004), sexual satisfaction (p=0.009) and overall sexual function index (p=0.04) in both groups, which were higher in the condoms-used group. There was a significant direct relationship between female sexual function index and satisfaction in the condom method (p=0.001, r=0.48) and the withdrawal method (p=0.001, r=0.38). Conclusions: Female sexual function and satisfaction in the users of male condoms is higher than the withdrawal method of contraception, while significant direct relationship was found between female sexual function and satisfaction in both methods. For a more detailed conclusion on female sexual function and satisfaction of users of these methods, longitudinal studies are suggested to be done by performing follow-up periods before, during and after cessation of method.